2013
DOI: 10.1016/j.bone.2013.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte regulation of phosphate homeostasis and bone mineralization underlies the pathophysiology of the heritable disorders of rickets and osteomalacia

Abstract: Although recent studies have established that osteocytes function as secretory cells that regulate phosphate metabolism, the biomolecular mechanism(s) underlying these effects remain incompletely defined. However, investigations focusing on the pathogenesis of X-linked hypophosphatemia (XLH), autosomal dominant hypophosphatemic rickets (ADHR), and autosomal recessive hypophosphatemic rickets (ARHR), heritable disorders characterized by abnormal renal phosphate wasting and bone mineralization, have clearly impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 49 publications
2
81
0
2
Order By: Relevance
“…Functionally, the expression of FGF23 in osteoblasts and osteocytes is controlled by FGFR1 signaling (Martin et al 2011), which in turn controls phosphate homeostasis and bone mineralization (Quarles 2012;Feng et al 2013). Low-molecular-weight FGF2 stimulates FGF23 promoter activity through PLCγ/NFAT and MAPK signaling, whereas high-molecular-weight FGF2 promotes FGF23 promoter activity through cAMP-dependent binding of FGFR1 and CREB to a conserved cAMP response element in the FGF23 promoter (Han et al 2015).…”
Section: Fgf/fgfr Signaling In Osteoblastogenesismentioning
confidence: 99%
“…Functionally, the expression of FGF23 in osteoblasts and osteocytes is controlled by FGFR1 signaling (Martin et al 2011), which in turn controls phosphate homeostasis and bone mineralization (Quarles 2012;Feng et al 2013). Low-molecular-weight FGF2 stimulates FGF23 promoter activity through PLCγ/NFAT and MAPK signaling, whereas high-molecular-weight FGF2 promotes FGF23 promoter activity through cAMP-dependent binding of FGFR1 and CREB to a conserved cAMP response element in the FGF23 promoter (Han et al 2015).…”
Section: Fgf/fgfr Signaling In Osteoblastogenesismentioning
confidence: 99%
“…The reason is that mutant form of FGF23 is resistant to proteolysis and it mainly remains as an intact protein, and this intact protein exerts the entire effects of FGF23 in cellular levels. 13,19 A study on large kindred affected by ADHR revealed that patients in their childhood had bone pain, short stature, lower extremity deformities, dental abscess, and rickets. The patients affected by ADHR in their adulthood had symptoms like tumor-induced osteomalacia (TIO).…”
Section: Autosomal Dominant Hypophosphatemic Ricketsmentioning
confidence: 99%
“…For instance, the inheritance pattern of male-to-male transmission, eliminates the possibility of XLH, while the presence of affected parent obviates the possibility of ARHR. 19 6. Treatments Available for Hypophosphatemic Rickets Phenotype heterogeneity is a common feature observed among patients with similar genotype.…”
Section: Molecular Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, phosphate homeostasis, destructed in XLH patients [25], is also connected to energy metabolism [26,27]. Phosphorus contributes to bone development and maintenance [28].…”
mentioning
confidence: 99%